The Examination of Risk Management in the Amateur Football Clubs Consisting of Student Players - Dilara Kubal,; Burkay Cevahircioğlu, (Journal of Educational Issues, 2024)
The aim of the study is to examine student football players’ perceived risk levels according to some variables. Descriptive survey model was used in the research. The research was applied on 240 students playing football in 1st amateur football league, Ordu. The ‘Risk Assessment Scale’ developed by Karataş (2012) was used as a data collection tool. The scale scores of the groups according to the independent variables were compared with the student t-test, one-way analysis of variance (ANOVA) and Tukey multiple comparison tests for unrelated samples in parametric data, and the Kruskal Wallis-H test and the Mann Whitney-U test with Bonferroni correction for non-parametric data. According to the results of the analysis, it was determined that the risk perception and evaluation levels of students differed significantly according to the variables of marital status, number of children, education level, family income level, place of birth and sports year (p < 0.05). However, it was determined that the risk assessment levels of the students did not differ significantly according to age, father and mother education level variables (p > 0.05). The findings reveal that the decrease in the monthly income level increases the risk perception levels of the students in the sports life. In addition, it was determined that as the education level of the students increased, their tendency to take risks also increased. According to the results of the research, it can be stated that the level of perceiving and analyzing risks of experienced students is higher than those of less experienced students.